Measured Catch Blue swimming crab (Portunus pelagicus) Based on the Walter-Hilbron Non-Equilibrium Model) Bangkalan Madura Waters - Siti Naviah; Samsul Huda; Dyah Arini (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
Blue swimming crab (Portunus pelagicus) as an export product relies mostly on catches, one of which is in Fishery Management Area 712, where this research was carried out. The frequency of fishing efforts continues to increase because of its high economic value; however, there is not much information about the resource as a basis for following up on Law Number 45 of 2009 concerning measurable fish catches based on control output. Descriptive research method with the aim of mapping crab resources based on the "Walter-Hilbron Non- Equilibrium Model" The results showed that the maximum catch production (CMSY) was 63,886.114 kg/year with standard Trammel net fishing gear, intrinsic growth was 50.91%/year, the carrying capacity of the waters was 50195,336 Kg/year, dominant species was Portunus pelagicus, Optimum effort (Eopt) 6363750 trip/year with a resource potential of 25097.668 kg/year. This information forms the basis for resource mapping in order to increase inclusive and sustainable economic growth.